1990
DOI: 10.1161/01.str.21.4.589
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic infarct induced by arterial hypertension in cat brain following middle cerebral artery occlusion.

Abstract: The purpose of this experiment was to determine whether an acute rise in brain perfusion pressure causes hemorrhagic transformation of an infarct without a reopening of the occluded artery. We raised the blood pressure of 22 cats by aortic obstruction 5-24 hours after transorbital middle cerebral artery clipping; hemorrhagic infarcts were induced in 11. Mean arterial blood pressure increased by 57.2 ±16.9 mm Hg (mean±SD) in the 11 cats with hemorrhagic infarcts and by 40.4 ±16.9 mm Hg in the 11 remaining cats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Since the diagnosis of haemorrhagic transformation was made from the CT scan performed 3-5 days after stroke onset in 32 out of 34 cases, a cause-effect relationship between elevated DBP values and haemorrhagic transformation could be assumed. Both experimental 39 and observational 8 studies have stressed the role of high blood pressure in the onset of an infarct, predisposing towards haemorrhagic transformation. Furthermore, excessively high BP values were associated with parenchymal haemorrhage in patients participating in clinical trials of recombinant tissue plasminogen activator.…”
Section: Discussionmentioning
confidence: 99%
“…Since the diagnosis of haemorrhagic transformation was made from the CT scan performed 3-5 days after stroke onset in 32 out of 34 cases, a cause-effect relationship between elevated DBP values and haemorrhagic transformation could be assumed. Both experimental 39 and observational 8 studies have stressed the role of high blood pressure in the onset of an infarct, predisposing towards haemorrhagic transformation. Furthermore, excessively high BP values were associated with parenchymal haemorrhage in patients participating in clinical trials of recombinant tissue plasminogen activator.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to a second theory suggesting the role of collateral circulation reperfusion injury. Ogata et al 25 indicated that HT may occur with persisting occlusion when infarcted areas are exposed to sufficient perfusion pressure from the leptomeningeal collaterals on the surface of the brain, the mechanism of which has also been demonstrated more recently in animal models 26…”
Section: Pathophysiologymentioning
confidence: 96%
“…5 The predisposing factor(s) responsible for HT are not well defined, although etiology (thrombotic versus embolic), [5][6][7] collateral circulation, 8,9 reperfusion, 10 hypertension, 6,8,[11][12][13] size of the ischemic lesion, 5,14 -20 and the use of anticoagulants, thrombolytics, [21][22][23][24] or both have been implicated. No precise predictors of HT have been determined, but caution is suggested when thrombolysis is considered in patients with early x-ray CT signs of major stroke such as sulcal effacement, mass effect, edema, or possible hemorrhage 25,26 or National Institutes of Health Stroke Scale score greater than 22.…”
Section: See Editorial Comment Page 151mentioning
confidence: 99%